Genome Sequencing Providing Molecular Evidence of Tetrapolar Mating System and Heterothallic Life Cycle for Edible and Medicinal Mushroom Polyporus umbellatus Fr. - Shoujian Li; Youyan Liu; Liu Liu; Bing Li; Shunxing Guo (Journal of Fungi)
Polyporus umbellatus is a species whose sclerotia have been extensively employed in traditional Chinese medicine, which has diuretic, antitumor, anticancer, and immune system enhancement properties. However, prolonged asexual reproduction has resulted in significant homogenization and degeneration of seed sclerotia. In contrast, sexual reproduction has emerged as an effective strategy to address these challenges, with a distinct mating system serving as the foundation for the implementation of sexual breeding. This study presents the first sequencing and assembly of the genome of P. umbellatus, thereby providing an opportunity to investigate the mating system at the genomic level. Based on the annotated mating-type loci within the genome, monokaryotic offspring exhibiting different mating-types were identified. Through the integration of traditional mating tests, the tetrapolar mating system of P. umbellatus was distinctly elucidated. The resequencing of monokaryotic strains with four different mating-types, along with comparative analyses of mating-type loci, revealed the HD1 and HD2 (HD, homeodomain) genes determined the mating A types, and the PR4, PR5, and PR6 (PR, pheromone receptor) genes determined the mating B types. Meanwhile, this study offers a successful case study in the molecular investigation of mating systems. Additionally, the number of sterigma and basidiospores on each basidium was examined using scanning electron microscopy, while the nuclei of basidiospores and basidia at various developmental stages were analyzed through DAPI staining. This research clarifies the heterothallic life cycle of P. umbellatus. The findings of this study are expected to facilitate advancements in genetic research, breeding development, strain improvement, and the industry of P. umbellatus.